Pearls are a girl's best friends: nostalgia and its discontents in the life-stories of two Georgian women - Eleni Sideri (IBSU Scientific Journal (IBSUSJ), 2009)
Natela remembers her femininity as an expression of a long Georgian national tradition that seems to be threatened by a new, market-oriented order. On the contrary, Dela is determined to take advantage of the emerging need for luxury goods and fashion trends among the female consumers in modern Tbilisi. My paper will focus on the life stories of these two Georgian women and will try to postulate how the generational differences have affected the perceptions of their past and future in Georgia. Which are the emerging social spaces where they feel included or excluded and why? How do personal or family memories interact with national history? In which ways are these memories materialized though material culture? To what degree do social and economic changes lead to reassessment of the value, economic and emotional, attached to material culture? Based on a multi-dimensional understanding of memory, the reference to the Georgian past for these two women is not a nostalgic journey to an uncontested time which is often the case in an official national history. They are both culturally aware agents that seem to challenge to different degrees and for different reasons the linearity of time and space, negotiating in this way the idea of a biography. Taking as start point these two life stories, I examine how the theme of nostalgia does not necessarily allude to a frozen in memory past, but it interacts with a real effort of assessing the present conditions of living and articulates complaints or desires for the future.
Keywords: 330; gender; material culture; memory; nostalgia; Georgia